Towards photonic biosensing using a three-port mach-zehnder interferometer in a silicon nitride platform - Leuermann, Jonas; Fernández-Gavela, Adrián; Lechuga, Laura M.; Sánchez-Postigo, Alejandro; Molina-Fernández, Íñigo; Halir, Robert (My University, 2018)
Integrated photonics enables sensitive and label-free optical biosensors for the detection of chemical and biological substances and is therefore promising for future lab-on-chip solutions. In this article we present our current development of silicon nitride based integrated photonic biosensing devices working at telecom wavelengths. Our approach of three-port based interferometric sensing circumvents the issues of conventional Mach-Zehnder interferometers, providing a constant sensitivity, and allowing to use a fixed wavelength sensing scheme. Preliminary experimental results show that the fabricated devices work as expected from simulations.
Keywords: Telecomunicaciones - Congresos; Óptica integrada - Congresos